The old open clusters Saurer A, B and C revisited - Carraro, Giovanni (2003)
We report deep (V ≈ 24.0) VI CCD photometry of three fields centred in the regions of the old open clusters Saurer A, B and C. In the case of Saurer A, which is considered one of the oldest known open clusters, we also provide a comparison field. From the analysis of the photometry we claim that Saurer A is as old as M67 (≈5 Gyr), but more metal-poor (Z = 0.008). Moreover, it turns out to be the open cluster with the largest galactocentric distance so far detected. As for Saurer B, it closely resembles NGC 2158, and indeed is of intermediate age (1.8-2.2 Gyr) and significantly reddened. In this case we revise both the age and the distance with respect to previous studies, but we are not able to establish clearly the cluster metal abundance. Finally, Saurer C has an age of about 2 Gyr, but we emphasize that the precise determination of its properties is hampered by the heavy field star contamination. All of the photometry is available at the WEBDA data base: http://obswww.unige.ch/webda/navigation.html.